Towards a New ASEAN Regionalism: Navigating the Outlook on Indo-Pacific in Post-RCEP Beyond 2020 - Hino Samuel Jose; Hree Dharma Santhi Putri Samudra (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
The adoption of the Regional Comprehensive Economic Partnership (RCEP) has brought the Asia Pacific region into a new paradigm of ASEAN regionalism. The global economic competition between China and the western world significantly impacts Southeast Asian countries regionally due to geographical factors and regional integration towards the ASEAN community. The changing regional order then happened after RCEP increased China's interest in the Southeast Asian geopolitical landscape and ASEAN – China's role in post-pandemic global governance. The authors discussed how China's soft power influences ASEAN's regionalism through the RCEP and vice versa. Further, it investigates how the dynamics impact the ASEAN Outlook on Indo-Pacific. Using the concept of soft power and institutional neoliberalism, this article has concluded that China is now ascending its inter-regional cooperation to capture a more significant interdependence to challenge the Western's rule of global order. The rivalry between the U.S. and China, ASEAN external partners, the Belt and Road Initiative (BRI), and the political cases concerning said stipulations of the AOIP hence identify the impacts and how ASEAN can navigate the region amid global uncertainties.